Există consens de a combate traficul de migranți în era digitală? [Articol] - Cojocari, Ion (CEP USM, 2021)
The article analyses the criminal legislation of the Republic of Moldova in relation to international standards for the protection of migrants’ rights. The article is an attempt to strike a balance between migrants’ access to privacy and the public interest in combating smuggling of migrants in the digital age. The search for consensus arises in response to the question of the extent to which the judicial act will have a higher level of legitimacy when the state has the broad margin of appreciation to assess the interference in the migrant’s private life in the internet.
IS THERE CONSENSUS TO COMBAT SMUGGLING OF MIGRANTS IN THE DIGITAL AGE?
Keywords: smuggling of migrants; digital age; private life; migrants; trafficking; penal code; the organisation of the illegal migration